The queen mother Jezebel: a rebuttal of the deuteronomistic bias. - Mwandayi, Canisius (VDM Verlag Dr. Müller GmbH & Co. KG, 2016)
This work is a look into one of the main areas of Old Testament study namely: the Deuteronomistic History. It focuses in particular on the presentation of the Queen Mother Jezebel by the Deuteronomistic redactor, exposing and refuting what I postulate was the redactor’ bias. The discrimination of women is not a yesteryear phenomenon nor is it confined to one locality. Down the corridors of history women have suffered as much discrimination in the West as they do in the Third World in both Church and social life. To the dismay of many, however, this discrimination has often been the result of a certain interpretation of the Bible which on the surface appears to be quite justified. Faced with the masculo-centric language of the Biblical text, attempts have been made to fight this discrimination and these have actually seen the emergence of a feministic theology. Such a theology in a way attacks the Bible as well as the Church and insists that both must be changed. This approach has led to the widespread doctoring of the English language as a result of the double use to which the word ’man’ can be put. At the bottom of it, however, lies the failure to recognise that the Bible's use of masculine nouns and pronouns is not sexist but inclusive. Western languages, for example, Hebrew, Greek, English, German and others which are masculine languages use the terms ‘male’ as inclusive of ‘woman’ and the pronoun ‘he’ as inclusive of ‘she’. Though not overlooking the limitations of this feministic interpretation of the Bible, reformist or liberal feminists in a way are right when they advocate that certain passages of the Biblical text that are gender sensitive need reinterpretation. A rewording, in other words, of the offending passages into a language that shows full appreciation for men as well as women is really called for.